Analysis of subjective responses for the evaluation of the indoor environmental quality of an educational building. (7th February 2020) - Pistore, Lorenza; Pittana, Ilaria; Cappelletti, Francesca; Romagnoni, Piercarlo; Gasparella, Andrea
Abstract : This article presents a method to conduct non-invasive subjective surveys applied to the evaluation of the indoor environmental conditions of a secondary school building by means of students' subjective responses. The case study is a secondary school in Treviso (Italy). Field campaigns have been carried out three times during the heating season 2016-2017 in seven among thirty classrooms, in order to conduct the evaluation in representative conditions limiting the interference with teachers' and students' activities. Students were asked to assess their overall satisfaction about the environment, their behavior towards discomfort and their interactions with the building and the systems. A specific questionnaire has been developed paying particular attention to the occupants' target and to the questions intended to grasp not only the comfort feedbacks, but also the interactions and the individual students' attitudes that can influence the building energy performance. The students' satisfaction has been analyzed for all the comfort areas (i.e., thermal, visual, acoustic and air quality) applying the method proposed by the technical standard EN 15251 for thermal comfort and extending it to all the other comfort aspects. Then, statistical tests have been implemented in order to investigate the significance of the date chosen for administering the surveys, the classrooms' location inside the building (e.g., orientation and level) and the heating system with the thermal satisfaction and sensation. Subjective responses have also been used to understand the perceived causes of discomfort and to assess if students aged from 14 to 19 years old react to discomfort or if they are subjected to it without taking actions. Despite the great variability of the percentages of satisfied people in the selected classrooms, the statistical tests performed on satisfaction and sensation votes regarding thermal environment have shown that the day of the survey has a higher impact on the evaluation than the floor level or the type of heating system. Finally, the analysis reveals that students of secondary schools tend to rely on the teacher to adjust uncomfortable conditions.